2022
DOI: 10.1111/jdi.13732
|View full text |Cite
|
Sign up to set email alerts
|

Young‐onset diabetes patients in Thailand: Data from Thai Type 1 Diabetes and Diabetes diagnosed Age before 30 years Registry, Care and Network (T1DDAR CN)

Abstract: Aims/Introduction There is a lack of current information regarding young‐onset diabetes in Thailand. Thus, the objectives of this study were to describe the types of diabetes, the clinical characteristics, the treatment regimens and achievement of glycemic control in Thai patients with young‐onset diabetes. Materials and Methods Data of 2,844 patients with diabetes onset before 30 years‐of‐age were retrospectively reviewed from a diabetes registry comprising 31 hospitals in Thailand. Gestational diabetes was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The disease burden attributable to diabetes increased in middle-aged groups and elderly groups from 1990 to 2019. Therefore, age represents a risk factor for diabetes; this finding was consistent with the findings of most previous studies [ 36 38 ]. These findings indicated that the disease burden gradually increased with age growth.…”
Section: Discussionsupporting
confidence: 92%
“…The disease burden attributable to diabetes increased in middle-aged groups and elderly groups from 1990 to 2019. Therefore, age represents a risk factor for diabetes; this finding was consistent with the findings of most previous studies [ 36 38 ]. These findings indicated that the disease burden gradually increased with age growth.…”
Section: Discussionsupporting
confidence: 92%
“… 2 The prevalence of T1D in Thai was 62.6% of patients with diabetes onset before 30 years of age. 3 The possibility of other types of diabetes should be considered clinically relevant in a child who does not have autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…DM stands as a leading cause of death in Thailand, accounting for approximately 15% of the 200,000 chronic non-communicable disease related deaths in 2016 7 . Various factors have been associated with DM risk, including sex, advancing age, high body mass index, stress level, smoking cigarettes, alcohol consumption, and fatty liver disease (FLD) [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%